Behavioral Responses to Barriers by Desert Tortoises: Implications for Wildlife Management - Ruby, Douglas E.; Spotila, James R.; Martin, Stacia K.; Kemp, Stanley J. (Allen Press, 1994)
We conducted tests on the behavioral responses of captive desert tortoises (Gopherus agassizii) to barriers and highway obstacles. Desert tortoises are slow-moving but persistent wanderers in their natural habitat. Consequently, they move substantial distances when they meet a barrier that they cannot go around. Tortoises responded differently to solid and non-solid barriers when placed in small pens constructed of various materials. Our tests indicated that a screen mesh with small enough openings to exclude a tortoise's head was the most suitable barrier material. When tortoises were tested for 2 h periods or after an overnight stay in a barrier pen, rates of responses with barriers declined with time but tortoises continued movement along the barrier. In a choice situation, we found no preference by tortoises for following either solid or mesh barrier fences. Tortoises quickly walked past openings in a barrier which were too small to enter but easily escaped from a barrier pen within 30 min when openings of an appropriate size were available. We found tortoises willingly entered culverts under large highways and retreated from concrete highways barriers.
Keywords: Barriers; Behavior; Desert tortoise; Fences; Gopherus agassizii; Testudinadae